2021
DOI: 10.1021/acs.orglett.1c01745
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative N-Alkylation of Azoles through Visible-Light-Mediated Organophotoredox Catalysis

Abstract: An organophotoredox-catalyzed decarboxylative cross-coupling between azole nucleophiles and aliphatic carboxylic acid-derived redox-active esters is demonstrated. This protocol efficiently installs various tertiary or secondary alkyl fragments onto the nitrogen atom of azole nucleophiles under mild and transition-metal-free conditions. The pyridinium additive successfully inhibits the formation of elimination byproducts from the carbocation intermediate. This reaction is applicable to the synthesis of a protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
(16 reference statements)
0
20
0
1
Order By: Relevance
“…Recognizing the inherent scarcity of versatile catalytic methods that are available to form carbon–heteroatom bonds directly from carboxylic acids, , we initiated a program to develop a platform of reactivity in which carbocations could be generated directly from carboxylic acids (Figure B). We were encouraged by work from Ohmiya and Nagao who recently demonstrated that redox-active esters could be used as carboxylic acid surrogates for coupling with alcohols to form ethers under photocatalytic conditions. , Additionally, Baran and co-workers reported an elegant electrochemical approach for C–O coupling via carbocation intermediates . Nevertheless, additional platforms that employ mild photochemical conditions would greatly expand the utility toward medicinal chemistry and chemical biology applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the inherent scarcity of versatile catalytic methods that are available to form carbon–heteroatom bonds directly from carboxylic acids, , we initiated a program to develop a platform of reactivity in which carbocations could be generated directly from carboxylic acids (Figure B). We were encouraged by work from Ohmiya and Nagao who recently demonstrated that redox-active esters could be used as carboxylic acid surrogates for coupling with alcohols to form ethers under photocatalytic conditions. , Additionally, Baran and co-workers reported an elegant electrochemical approach for C–O coupling via carbocation intermediates . Nevertheless, additional platforms that employ mild photochemical conditions would greatly expand the utility toward medicinal chemistry and chemical biology applications.…”
Section: Introductionmentioning
confidence: 99%
“…Алкилирование азотистых гетероциклов обычно протекает легко по атому азота кольца: так алкилируются как азины, например, производные пиридина и пиримидина [8], так и атомы азота пятичленных азолов [9]. В случае азолопиримидинов, содержащих оба типа ароматических гетероциклов, реакции могут протекать как по атому азота пиримидинового, так и пятичленного колец [10].…”
unclassified
“…These reagents then gave the corresponding pyrrolidines bearing C-4 and C-5 substituents in good yields and modest d.r. (17)(18)(19)(20)(21)(22)(23). The synthesis of an ⍺-arylated proline derivative 22 from an Laspartic acid derived annulation reagent and a densely functionalized spirocyclic pyrrolidine 23 proceeded in 70% and 54% yield, respectively.…”
mentioning
confidence: 99%